Chronology of Religious Discourse in Algeria: Reality and Challenges - ben ali, mohamed (Journal of Social Sciences and Humanities, 2024)
The purpose of this contribution is to reveal the path of religious discourse in Algeria. As well as the expected internal and external challenges. As we entered the stage of the new media, it became clear that we were facing a real challenge with the incoming religious discourses, which posed a threat to the coherence of our religious authority and affected the stability and security of society. It is clear that we are in an open confrontation from two angles: an internal angle that requires crystallizing a creative vision for our religious discourse according to our national reference. And an external angle imposes addressing violence and hate speech. To address these issues, we will ask the following questions: What is the truth about religious discourse in Algeria? Is he able to adapt his methods to face the reality that threatens him? What are the mechanisms of expected renewal?